NASKAH PUBLIKASI âPENGARUH TATA KELOLA PERUSAHAAN, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016â - Novita Putri Riandani, 14.05.52.0162; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2018)
This study examines the effect of corporate governance, capital structure, and company size of the earnings management on the manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2016. This study used purposive sampling method in sample selection, the criteria for a sample of the manufacturing companies listed in Indonesia Stock Exchange (IDX) during the period 2013-2016. Based on these criteria, obtained a sample of 120 companies over a four-year observation period. relationship and or influence between variables explainned by using logistic regression analysis method. The result of reseacrh indicate that audit commite variable and managerial ownership have positive effect not significant to earnings management, independent commissioner variable has no significant effect on earnings management, the variable of institutional ownership and capital structure have a significant positive effect on earnings management, and firm size variable have a significant negative effect to earnings management.Keywords: earnings management, audit commite, independent commisioner, institutional ownership, managerial ownership, capital structure, firm size.